Chemical and sensory characteristics of sweet potato crackers containing various starch types - Aini, Nur; Husna, Syifaul; Indarto, Indarto; Waziiroh, Elok; Probowati, Banun Diyah; Setyawati, Retno; Arsyistawa, Hadana Sabila; Fitriati, Annisa (AGROINTEK, 2025)
White sweet potato is a local Indonesian food ingredient that can be processed into various products, including nonflaky crackers. Adding different types of starch to the cracker formulation can improve product characteristics, enhancing sensory acceptability. This study aims to determine the effects of the proportion of white sweet potato flour to wheat flour and the type of added starch on the chemical and sensory characteristics of crackers. A completely randomized design (CRD) was used. The factors studied were the addition of various types of starch (P; P1, white sweet potato starch; P2, cornstarch; and P3, tapioca) and the white sweet potato starch: wheat flour ratio (% w/b, T) (T1, 1:3; T2, 1:1; T3, 3:1; and T4, 4:0). The chemical characteristics evaluated were the moisture, ash, fat, protein, and carbohydrate contents. The sensory characteristics evaluated were the taste, texture, color, and degree of liking (preference). The chemical variables were analyzed using ANOVA and DMRT at the α = 5% level. The Friedman test was used for sensory evaluation. The results showed that the type of added starch (P) significantly affected the fat content. Furthermore, the proportion of white sweet potato flour to wheat flour (T) significantly influenced the fat and protein contents. In addition, the treatment combination (PT) significantly affected texture, color, and preference. The best treatment (P1T1) resulted in crackers with 4.40% moisture, 18.06% fat, and 74.86% carbohydrates, along with favorable sensory attributes like slightly salty taste, crunchy texture, and light brown color.